2010
DOI: 10.4238/vol9-4gmr875
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in wild species of passion fruit (Passiflora trintae) based on molecular markers

Abstract: ABSTRACT. In spite of the importance of and the considerable variability observed in Passiflora (Passifloraceae), little is known about the genetic diversity of most of the species of this genus. We evaluated the genetic diversity by RAPD markers in 18 genotypes of Passiflora trintae. The 15 primers generated 112 markers, 84% of which were polymorphic. The genetic distance estimated by the complement of the Dice index (average dissimilarity = 0.30) and genotype grouping based on the UPGMA algorithm showed low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Bellon et al (2005), who working with P. alata observed high variability (an average number of 12.05 bands per primer) and Cerqueira-Silva et al (2010b), who working with P. tritae observed an average number of 7.46 bands per primer. With the commercial species P. edulis, Bellon et al (2007) observed an average number of 14.4 bands per primer, while Cerqueira-Silva et al (2010a) studying the same species observed a lower average number of bands per primer (5.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bellon et al (2005), who working with P. alata observed high variability (an average number of 12.05 bands per primer) and Cerqueira-Silva et al (2010b), who working with P. tritae observed an average number of 7.46 bands per primer. With the commercial species P. edulis, Bellon et al (2007) observed an average number of 14.4 bands per primer, while Cerqueira-Silva et al (2010a) studying the same species observed a lower average number of bands per primer (5.7).…”
Section: Resultsmentioning
confidence: 99%
“…In molecular diversity characterizations, RAPD markers (random amplified poly-morphic DNA) (Williams et al, 1990) have been widely used in Passiflora species, such as P. alata (Bellon et al, 2005), P. edulis Sims (Bellon et al, 2007;Cerqueira-Silva et al, 2010a), P. trintae (Cerqueira-Silva et al, 2010b), and Passiflora spp (Viana et al, 2010). We quantified, by RAPD markers and complement of the Dice index, the dissimilarity of wild genotypes of 'sleep' passion fruit, originating from the region of Vitória da Conquista, Bahia, Brazil, and belonging to the CAGT-Passiflora/UESB 'Planalto de Conquista'.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported attempts to clearly demarcate the species of the Passiflora genus using restriction enzymes (cpDNA sites; Yockteng and Nadot [17]; Paikrao et al [18]), amplified fragments length polymorphism markers (AFLP; Ortiz et al [4]; Segura et al [15]), microsatellite markers (SSR; Ortiz et al [4]; Oliveira et al [19]), and inter-simple sequence repeats (ISSR; dos Santos et al [11]). However, the genetic diversity of Passiflora species is mostly estimated with random amplified polymorphic DNA (RAPD; Fajardo et al [20]; Aukar et al [21]; Crochemore et al [22]; Cerqueira-Silva et al [23]).…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic variability can only be used efficiently if properly assessed and quantified. Thus, the germplasm must be characterised according to several morphological traits (Crochemore et al 2003;Plotze et al 2005;Bellon et al 2009;Viana et al 2010), agronomic behaviour (Cerqueira-Silva et al 2008;Abreu et al 2009) and molecular diversity (Cerqueira-Silva et al 2009;Cerqueira-Silva et al 2010;Viana et al 2010), enabling advances in the description of genetic divergence among accessions. Molecular markers have been used in plant breeding and in activities related to the conservation of genetic resources.…”
Section: Introductionmentioning
confidence: 99%